The antioxidant function of the p53 tumor suppressor - Sablina, Anna A. (2005)
It is widely accepted that the p53 tumor suppressor restricts abnormal cells by induction of growth arrest, or by triggering apoptosis. Here we show that in addition p53 protects the genome from oxidation by reactive oxygen species (ROS), a major cause for DNA damage and genetic instability. In the absence of severe stresses relatively low levels of p53 are sufficient for up-regulation of several antioxidant genes, which is associated with a decrease in intracellular ROS. Down-regulation of p53 results in excessive oxidation of DNA, increased mutation rate, and karyotype instability, which are prevented by incubation with antioxidant N-acetylcysteine (NAC). Dietary supplementation with NAC prevents frequent lymphomas characteristic to p53 knockout mice, and slows down growth of xenografts from A549 cells with p53 inhibited by siRNA. Our results provide novel paradigm for a non-restrictive tumor suppressor function of p53 and highlight potential importance of antioxidants in prophylactics and treatment of cancer.